Complications following local anaesthetic transperineal prostate biopsies without antibiotic prophylaxis: An institution's experience. (September 2022) - John, Joseph B; MacCormick, Angus; MacDonagh, Ruaraidh; Speakman, Mark J; Vennam, Ramesh; Burns-Cox, Nicholas
Objectives: This study aimed to describe a UK institution's experience with local anaesthetic (LA) transperineal (TP) prostate biopsies (PB), and to report 30-day complications following LATPPB, including a large cohort that did not receive antibiotic prophylaxis. Patients and methods: A prospective database of 313 consecutive patients undergoing LATPPB was maintained, describing patient and disease characteristics, and complications. From September 2019 to January 2020, antibiotic prophylaxis was given before LATPPB ( n =149). Following a change to routine care, from January 2020 to July 2020, prophylactic antibiotics were not given before LATPPB ( n =164). A comparative analysis was performed to determine complication rates following antibiotic prophylaxis discontinuation using electronic hospital and primary care records. Results: Patient and disease characteristics were comparable in antibiotic and non-antibiotic cohorts, and representative of PB and prostate cancer cohorts described in the urological literature. The infection-related complication rate was 0.32% across all patients, and 0% for those not receiving antibiotic prophylaxis. The overall complication rate was 0.64%, and 0.61% for those not receiving antibiotic prophylaxis. There were no severe (Clavien–Dindo 3–5) complications. The unplanned hospital admission rate was 0.64%. Conclusion: The complication rate after LATPPB was low, with no infection-related complications in patients who did not receive antibiotic prophylaxis. This provides further evidence supporting the discontinuation of routine prophylactic antibiotics before TPPB. Level of evidence: Level 2b.